2023
DOI: 10.1186/s12905-023-02275-6
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic variations of breast cancer treatment and discontinuation: a study from a public tertiary cancer hospital in Mumbai, India

Abstract: Background The study examined the socio-economic variation of breast cancer treatment and treatment discontinuation due to deaths and financial crisis. Methods We used primary data of 500 patients with breast cancer sought treatment at India’s one of the largest cancer hospital in Mumbai, between June 2019 and March 2022. This study is registered on the Clinical Trial Registry of India (CTRI/2019/07/020142). Kaplan–Meier method and Cox-hazard regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A total of 71 patients did not complete the treatment due to death or financial and other reasons. 31 Supplementary Table S2 shows the summary characteristics of the 429 patients in the concluded sample. A majority of the patients were married and from rural areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 71 patients did not complete the treatment due to death or financial and other reasons. 31 Supplementary Table S2 shows the summary characteristics of the 429 patients in the concluded sample. A majority of the patients were married and from rural areas.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the study design and sample design, including inclusion and exclusion criteria, can be found elsewhere. 31 …”
Section: Methodsmentioning
confidence: 99%